Gamearte com interação assimétrica: Thanatophobia - Lemos, Cássio Fernandes (2019)
The present dissertation in visual poetics deals with the production of the gameart "Thanatophobia", developed in the Graduate Program in Visual Arts / UFSM, in the line of research in Art and Technology, which consists of an artistic game realized in mixed reality. The gamearte approaches the characteristics common to the games, but is sustained by means of his poetics. It presents elements for interaction in a virtual environment, as well as uses physical interfaces, thus establishing an asymmetric interaction. This concept of asymmetric interaction, as pointed out in this research, concerns the participation of several interactors in different technological environments, each acting in a specific way according to each interface, yet exploiting the same virtual environment and shared actions. The theme of the artgame "Thanatophobia" is terror, being recurrent in several artistic works. Here, terror has a strong connection with the immersion of the interactors in a hostile environment, provoking different sensations, being fear the main of them. In order to establish such connections between game, art and terror, we investigate the concepts of games and gamearte, their relationship with the field of arts, interface and interactivity issues, as well as a reflection on asymmetric interaction from the development of the poetics of the artgame "Thanatophobia".